Building a resilient twenty-first-century economy for rural America - Albrecht, Don E. (Utah State University Press, an imprint of University Press of Colorado, 2020)
"Rural communities have traditionally been dependent on goods-producing industries. What happened as employment in these industries has declined? Provides a path a twenty-first-century economy can be built. Describes how economic changes led rural voters to support Trump and why his policies won't relieve rural economic problems"--